(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
In this article the data about collections on the territory of Ukraine of some interesting representatives of the genera Bolbitius and Pholiotina are presented. This is the result of investigation of specimens from the National herbarium of Ukraine (KW) as well as the author’s personal collections. As result, the data about both new for this country species (Bolbitius lacteus, Pholiotina parvula and P. sulcata) and unknown before locations of some already recorded here taxa (Bolbitius reticulatus, Pholiotina brunnea, P. coprophila, P. mairei and P. vestita) are obtained.